Construction of nitrogen-fixing Klebsiella variicola GN02 expression vector pET28a-Lac-EGFP and its colonization of Pennisetum giganteum z.x.lin roots. Issue 1 (1st January 2019) - Lin, Biaosheng; Chen, Yi; Zheng, Shizhong; Jia, Yulei; Wang, Lifang; Lu, Guodong; Lin, Zhanxi
Abstract: To explore the colonization of endophytic nitrogen-fixing bacterium Klebsiella variicola in Penniseum sinense, pET28a and the enhanced green fluorescent protein (EGFP) were used as basic elements to construct a recombinant expression vector pET28a-Lac-EGFP with the addition of starter Lac in pUC18 vector using enzymatic digestion and splicing methods. The constructed recombinant vector was transformed into K. variicola GN02 cells with electroporation method and the colonization of EGFP-tagged K. variicola GN02 in the roots of Pennisetum sp. was observed using laser confocal scanning microscopy. The results of restriction enzyme digestion and sequencing analysis indicated that pET28a-Lac-EGFP was successfully constructed and the target gene was successfully transferred into K. variicola GN02 cells. Positive colonies with obvious green fluorescence were observed under ultraviolet (UV) light. Sodium dodecyl sulphate-polyacrylamide gel-electrophoresis (SDS-PAGE) showed that expression of the EGFP-labelled target protein was also successfully induced in K. variicola GN02 cells. Root scanner and confocal microscopy showed that inoculation of K. variicola GN02 strain was more conducive to the root growth of P. sinense and K. variicola GN02 mainly colonized the endothelial layer of Pennisetum sp. roots. However, colonization with a small amount of K. variicola GN02 led to its concentration in the epidermis, middle column and ducts. Our findings suggest that the endophytic nitrogen-fixing bacterium K. variicola accumulates in plant roots and is subsequently dispersed, aggregated or even colonized in susceptible plants. Furthermore, we provided a theoretical basis for the practical used of K. variicola GN02-based microbial fertilizers in P. sinense and gramineous plants.